Outcomes of Children and Adolescents Admitted with Diabetic Ketoacidosis at Kenyatta National Hospital (KNH), Kenya - Sophie Nyaombe Musoma; Anjumanara Omar; Beatrice Chepngeno Mutai; Paul Laigong (Journal of Diabetes Research)
Background. Diabetic ketoacidosis (DKA) is an acute, major, life-threatening complication that mainly occurs in patients with type 1 diabetes mellitus and is the foremost cause of death in these children. Overall mortality in children with DKA varies from 3.4% to 13.4% in developing countries. There is a need to understand outcomes among children with DKA in sub-Saharan African countries. Objective. To determine the death rate and clinical outcomes of children and adolescents aged 0-18 years managed for DKA at Kenyatta National Hospital (KNH). Study Methods. This was a retrospective study carried out among children aged 0–18 years admitted with DKA at KNH between February 2013 and February 2018. The study site was the central records department at KNH. The inclusion criteria were children aged 0-18 years admitted with a diagnosis of DKA based on the ISPAD guidelines biochemical criteria. Results. Out of the 159 files reviewed, the median age of children was 13 years (IQR 10-15). 41.1% of patients had severe DKA while 35.7% had moderate DKA. We reported a mortality of 6.9% while 93.1% of children recovered and were discharged home. The median duration of hospital stay was 8 days. High risk of mortality was reported among children who had high serum creatinine (OR 5.8 (95% CI 1.6-21.2)), decreased urine output (OR 9.0 (95% CI 2.2-37.3)), and altered level of consciousness (OR 5.2 (95% CI 1.1-25.1)). Conclusion. DKA-associated mortality in our study was low at 6.9%. High serum creatinine, decreased urine output, and altered level of consciousness were associated with a significantly higher risk of mortality.